Prioritization method for frontier DMUs: a distance-based approach - Alireza Amirteimoori; Gholamreza Jahanshahloo; Sohrab Kordrostami (Journal of Applied Mathematics)
In nonparametric methods, if the number of observations is relatively small as compared to the sum of number of inputs and outputs, many units are evaluated as efficient. Several methods for prioritizing these efficient units are reported in literature. Andersen et al. and Mehrabian et al. proposed two methods for ranking efficient units, but both methods break down in some cases. This paper describes a new DEA ranking approach that uses L2-norm.